2022
DOI: 10.1021/acs.nanolett.2c02901
|View full text |Cite
|
Sign up to set email alerts
|

Improved Self-Heating in Short-Channel Monolayer WS2 Transistors with High-Thermal Conductivity BeO Dielectrics

Abstract: Two-dimensional semiconducting transition metal dichalcogenides (TMDs) enable ultimate channel length scaling of transistor technology due to their atomic-thin body nature, which also brings the challenge of a pronounced self-heating effect inside the ultrathin channel. In particular, high current density under high electric field could lead to negative differential resistance behavior due to self-heating, not only limiting the current carrying capability of the TMDs transistors but also leading to severe reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, in practical scenarios, it is often observed that I ds tends to decrease at high voltage after reaching a quasi-saturation point. The definition of NDR is the percentage of the difference between over saturation current and saturation current of the device Δ I ( Δ I = ( I ds – I sat )) and saturation current density I sat , i.e Δ I / I sat × 100%. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in practical scenarios, it is often observed that I ds tends to decrease at high voltage after reaching a quasi-saturation point. The definition of NDR is the percentage of the difference between over saturation current and saturation current of the device Δ I ( Δ I = ( I ds – I sat )) and saturation current density I sat , i.e Δ I / I sat × 100%. , …”
Section: Resultsmentioning
confidence: 99%
“…The definition of NDR is the percentage of the difference between over saturation current and saturation current of the device ΔI (ΔI = (I ds − I sat )) and saturation current density I sat , i.e ΔI/I sat × 100%. 39,40 As shown in Figure 1a, when MoS 2 devices are operated under high voltage, Joule heating is inevitably generated in the channel of the FET. It is obvious that the self-heating effect is ubiquitous in 2D FETs and has a significant influence on the saturation current and the stability of the device.…”
Section: ■ Introductionmentioning
confidence: 99%